2002
DOI: 10.1038/sj.cgt.7700470
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FGF receptor-binding peptides for cancer gene therapy

Abstract: Linear FGF receptor -binding heptapeptides were identified by phage display using sequential rounds of biopanning against cells with displacement of phage by FGF2. The consensus motif MXXP was iterated after four to five rounds and the peptide MQLPLAT was studied in depth. Phage bearing MQLPLAT showed high levels of binding to FGF receptor positive cells, with over 90% of phage bound being eluted competitively by adding free FGF2. MQLPLAT phage showed only limited binding to Cos7 cells deficient in receptors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 23 publications
0
49
0
1
Order By: Relevance
“…184 A study demonstrated that a heptapeptide sequence (MQLPLAT) is binding to FGFR with high affinity, 185 suggesting that peptide is also a ligand to FGFR. Hu et al 186 …”
mentioning
confidence: 99%
“…184 A study demonstrated that a heptapeptide sequence (MQLPLAT) is binding to FGFR with high affinity, 185 suggesting that peptide is also a ligand to FGFR. Hu et al 186 …”
mentioning
confidence: 99%
“…In vitro biopanning was carried out as described previously with slight modifications (10)(11)(12). Briefly, following subtractive clearance of the library using the normal cell line MMNK-1, 3 consecutive rounds of in vitro biopanning were carried out on the target human ICC RBE cells.…”
Section: Identification Of Peptide Motifs Binding To Human Cca Rbe Cellsmentioning
confidence: 99%
“…Biopanning was conducted for a total of 3 rounds for enrichment of peptides binding selectively and efficiently to CCA. Phage display, isolation, and sequencing of phage DNA were carried out as described previously (10,11).…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17] There is considerable interest, therefore, in the use of such peptides as Ag-targeting moieties, since they could greatly simplify vaccine development. A receptor attracting considerable interest for enhancing Ag-specific immunity by targeting of Ag to DCs is CD11c/CD18, which is expressed at high levels on murine DCs, and is often used as DC-specific marker.…”
mentioning
confidence: 99%